Willingness to communicate in the L2 about meaningful photos: Application of the pyramid model of WTC. (November 2021) - MacIntyre, Peter D.; Wang, Lanxi
Willingness to communicate (WTC) reflects an intersection between instructed second language acquisition and learner psychology. WTC results from the coordinated interaction among complex processes that prepare second language (L2) learners to choose to use their L2 for authentic communication. Prior research has revealed considerable complexity in the influences on dynamic changes in WTC from moment-to-moment. The heuristic 'pyramid model' of WTC (MacIntyre et al., 1998) proposes interactions among approximately 30 different variables that may influence WTC. The present study uses the pyramid model to interpret data from three focal participants, all English as a second language (ESL) learners and international students in Canada, with varying degrees of experience in an English-speaking context. Using the idiodynamic method, all participants were recorded while describing a self-selected, personally meaningful photo. Second, participants rated their WTC in English using software that played a recording of their speech and collected continuous WTC ratings. Finally, participants were interviewed about their WTC ratings. Triangulating the data revealed how processes on multiple timescales interact during L2 communication about the photos. WTC changes as speakers' motivations and emotions are influenced by the deep, personal relevance of the topics under discussion. Pedagogical implications for the results of this study and the use of the idiodynamic method in L2 classrooms are discussed.